2D Bilinear programming for robust PID/DD controller design. (20th June 2016) - Hosoe, S.; Tuan, H. D.; Nguyen, T. N.
Summary: A new design method of PID structured controllers to achieve robust performance is developed. Both robust stabilization and performance conditions are losslessly expressed by bilinear constraints in the proportional‐double derivative variable (k P, k D D ) and the integral‐derivative variable (k I, k D ). Therefore, the considered control design can be efficiently solved by alternating optimization between (k P, k D D ) and (k I, k D ), which is a 2D computationally tractable program. The proposed method works equally efficiently whenever even higher order differential or integral terms are included in PID control to improve its robustness and performance. Numerical examples are provided to show the viability of the proposed development. Copyright © 2016 John Wiley & Sons, Ltd.